Atypical Anxiety-Related Amygdala Reactivity and Functional Connectivity in Sant Mat Meditation - Chen, Chenyi; Chen, Yu-Chun; Chen, Kuan-Ling; Cheng, Yawei (Frontiers in Behavioral Neuroscience, 2018)
While meditation has drawn attention in cognitive neuroscience, the neural mechanisms underlying emotional processing remains elusive. Recruiting Sant Mat meditators, who adopt loving-kindness meditation along with vegetarian diet and alcohol-restricted lifestyle, and novices, we assessed their State-Trait Anxiety inventory (STAI) and scanned their amygdala reactivity in response to explicit and implicit (backward masked) perception of fearful and happy faces. As compared with novices, meditators reported lower STAI scores. Meditators showed stronger amygdala reactivity to explicit happiness than fear, whereas novices exhibited the opposite pattern. Amygdala reactivity was reduced in meditators regardless of implicit fear or happiness. Those who spent more lifetime practice in meditation reported lower STAI and showed weaker amygdala response to fear. Furthermore, the amygdala in meditators relative to novices had a stronger positive functional connectivity with the ventrolateral prefrontal cortex to explicit happiness but a more negative connectivity with the insula and medial orbitofrontal cortex to explicit fear. Mediation analysis indicated the amygdala reactivity as the mediator for the linkage between meditation experience and trait anxiety. The findings demonstrate neural correlates underpinning the salubrious effect of meditation in Sant Mat. Long-term meditation could be functionally coupled with amygdala reactivity to explicit and implicit emotional processing, which would help reduce anxiety and potentially enhance well-being.